2008
DOI: 10.1158/1055-9965.epi-08-0010
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A/p16 Genetic Test Reporting Improves Early Detection Intentions and Practices in High-Risk Melanoma Families

Abstract: Genetic testing for melanoma has yet to enter routine clinical use because of the scarcity of available data on the effect of test reporting. A prospective study of 59 members of Utah CDKN2A/p16 mutation-positive pedigrees was conducted to establish the effect of CDKN2A/ p16 genetic test reporting on melanoma early detection intentions and behaviors (total body skin examination and skin self-examination) in a high-risk population. Behavioral assessments were made at baseline, immediately after CDKN2A/p16 test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 35 publications
1
72
1
1
Order By: Relevance
“…Furthermore, this research study concluded that test reporting did not decrease the level of adherence for those who tested negative for the CDKN2A/p16 mutation previously identified in their family. The participants in this study had a family history of melanoma, and these results suggest a positive impact of genetic test reporting and counseling on patient behavior beyond what was motivated based on family history and independent of the test result itself [30]. Additional analysis of this sample population also found that the degree of photoprotection increased among both those who tested positive and negative for a CDKN2A/p16 mutation.…”
Section: Genetic Counseling and Testingmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, this research study concluded that test reporting did not decrease the level of adherence for those who tested negative for the CDKN2A/p16 mutation previously identified in their family. The participants in this study had a family history of melanoma, and these results suggest a positive impact of genetic test reporting and counseling on patient behavior beyond what was motivated based on family history and independent of the test result itself [30]. Additional analysis of this sample population also found that the degree of photoprotection increased among both those who tested positive and negative for a CDKN2A/p16 mutation.…”
Section: Genetic Counseling and Testingmentioning
confidence: 57%
“…However, the currently available data do not support these concerns. A research study performed by Aspinwall, et al in 2008 to assess the clinical utility of CDKN2A/ p16 genetic testing showed how test result reporting led to significant positive changes in the intention and magnitude of intention to screen between baseline, immediately following results disclosure, and one month post-reporting amongst high risk patients. Furthermore, this research study concluded that test reporting did not decrease the level of adherence for those who tested negative for the CDKN2A/p16 mutation previously identified in their family.…”
Section: Genetic Counseling and Testingmentioning
confidence: 99%
“…Selon une enquête menée en 2002 auprès de dermatologues hospitaliers français, la connaissance du statut « muté » motive les familles pour la prévention solaire et la surveillance. Le bénéfice du test génétique est confirmé par des études menées en Suède [5], en Hollande [6,7] et aux États-Unis, celles-ci ayant de plus montré qu'il n'y avait pas d'impact sur la motivation des patients non-porteurs de mutation [8][9][10]. En Australie [11][12][13] et en Suède [14], les tests génétiques sont plutôt bien acceptés et n'induisent pas de souffrance psychologique notable.…”
Section: Préambule à La Prescription Des Tests Génétiques Et Méthodolunclassified
“…These studies have suggested that genetic testing results in more appropriate screening and surveillance practices after disclosure (46)(47)(48)(49). That is, carriers increase their use of screening and noncarriers reduce their frequency of engagement in screening to fall into line with recommendations.…”
Section: Cancer Screeningmentioning
confidence: 99%